PEDAGOGICAL CONTENT AND PRACTICAL SITUATION OF IMPROVING STUDENTS' KNOWLEDGE OF THE CONCEPT OF TECHNOLOGICAL DETERMINISM (Scientific journal of the Fergana State University, 2023)
In this article, the content of technological education in higher technical education institutions is deeply embedded in students, while explaining the approaches to the perspectives of technical education, in particular, teaching approaches within the concept of technological determinism and technostatic determinism, through which technology and linking technological development to the chains of cause and effect in society, understanding technological development through the harmony of cause and effect, improving the methodology of teaching the system of views in this regard are widely covered.